Soil organic matter mineralization under different temperatures and moisture conditions in Kızıldağ Plateau, Turkey - Cenkseven, Sahin; Kizildag, Nacide; Kocak, Burak; Sagliker, Husniye Aka; Darici, Cengiz (Penerbit Universiti Kebangsaan Malaysia, 2017)
Drought by climate change in East Mediterranean Region will change soil temperature and moisture that lead to alter the cycling of biological elements like carbon and nitrogen. However, there are few studies that show how sensitivity of soil organic matter mineralization to temperature and/or moisture can be modified by changes in these parameters. In order to study how these changes in temperature and moisture affect soil carbon and nitrogen mineralization, a laboratory experiment was carried out in two depths (0-5 and 5-15 cm) of soils of Onobrychis beata and Trifolium speciosum being common annual plants in Turkey that was taken from Kızıldag Plataeu (Adana city). Some soil physical and chemical properties and as well as rate of carbon and nitrogen mineralizations were determined for both depths of soils. These soils were incubated for 42 days under different field capacities (FC 60, 80 and 100%) and temperatures (24, 28 and 32°C). Cumulative carbon mineralization (Cm), potential mineralizable carbon (C0) and rate of carbon mineralization of all soils were increased with rising temperatures. Rate of carbon mineralization in O. beata soil were lower than T. speciosum soil. NH4-N and NO3-N contents at 42nd day were higher than initial levels of soils and also increased with temperatures and field capacities. In summary, sensitivity of soil organic matter mineralization to temperature was higher at 32°C in upper layer and lower at 24°C in deeper layer of both soils.